Two level security for medical images using watermarking/encryption algorithms. Issue 1 (March 2014) - Kannammal, A.; Subha Rani, S.
ABSTRACT In this article, an attempt is made to provide two level securities for medical images using watermarking and encryption. Watermarking provides security and encryption, authenticates medical image and provides integrity. Watermarking is performed by using a new nontensor product wavelet filter banks, which have the ability to reveal singularities in different directions. Natural image is taken as the original image and the medical image is taken as a watermark image. The medical image is embedded into the LH sub band of the natural image. The encryption is performed by RSA, AES, and RC4 algorithms. A qualitative comparative analysis of the proposed algorithm is done for different encryption methods. The proposed algorithm has the ability to withstand different attacks like noise, rotation, contrast, and brightness attacks. Performance analysis is made by calculating PSNR, SSIM, NC, and CV.